Evaluation and Investigation of the Prevalence of Superficial Mycosis among Primary Schools Pupils in Al-Dewaniyah Governorate, Iraq - Sara K. Al-Zubaidi (Journal of Global Pharma Technology, 2016)
Background: The Superficial mycosis infections are the widespread types of mycosis among children primary schools. Objective: To detection and evaluation the extent and prevalence of superficial mycosis infection among primary school pupils in Al-Dewaniyah province. Subjects and methods: The survey included the selection of the pupils were randomly selected based on those with tinea (ringworm) lesions sample of 103 pupils (males 81, females 22) respectively from ten primary schools (six male and four female schools), they clinically diagnosis dermatophytoses, in the Diwaniyah Teaching Hospital, Dermatology unit, during a period from the beginning of December 2018 till the final February 2019. The specimens were collected in sterile plastic Petri dishes or sterile plastic envelopes and consisted of skin scales, hairs, or clippings from fingernails and toenails. The samples of fingernails and toenails were cut or to get mycelial elements. Results: The results of identity and incidence of the dermatophytes and non-dermatophytes isolated were revealed that dermatophytic isolation